Pieces and players - Balliett, Blue, 1955- (Scholastic Press, 2015)
"Thirteen extremely valuable pieces of art have been stolen from one of the most secretive museums in the world. ... Calder, Petra, and Tommy are no strangers to heists and puzzles. Now they've been matched with two new sleuths -- Zoomy, a very small boy with very thick glasses, and Early, a girl who treasures words . . . and has a word or two to say about the missing treasure. The kids have been drawn in by the very mysterious Mrs. Sharpe, who may be playing her own kind of game with the clues. And it's not just Mrs. Sharpe who's acting suspiciously -- there's a ghost who mingles with the guards in the museum, a cat who acts like a spy, and bystanders in black jackets who keep popping up"--Dust jacket.